1996
DOI: 10.1159/000127077
|View full text |Cite
|
Sign up to set email alerts
|

μ-Opioid Agonists Stimulate Growth Hormone Secretion in Immature Rats

Abstract: The purpose of the present study was to evaluate the opioid receptor subtype mediating opioid modulation of growth hormone (GH) secretion during ontogeny. The µ-agonist morphine and the Kagonist U50,488 caused a stimulation and inhibition of GH secretion, respectively, on postnatal day 10. Studies on postnatal days 2, 5, 10, 15 and 20 showed that ĸ-inhibition could be observed as early as day 2, but substantial µ-stimulation was not observed until postnatal day 10. Intracerebroventricular (i.c.v.) administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…But, in females, estrogen had an opposite effect as that for testosterone in males and when naloxone administered to immature female rats advanced the age of onset of puberty (17). This idea was repeated in ovariectomized rats when LH responses to opioids were antagonized by naloxone (18,19). In contrast to their effects on LH, most opioids and their analogs appear not to affect FSH (20).…”
Section: Discussionmentioning
confidence: 99%
“…But, in females, estrogen had an opposite effect as that for testosterone in males and when naloxone administered to immature female rats advanced the age of onset of puberty (17). This idea was repeated in ovariectomized rats when LH responses to opioids were antagonized by naloxone (18,19). In contrast to their effects on LH, most opioids and their analogs appear not to affect FSH (20).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, chronic administration has led to no (61,80) or to stimulatory effect (81). Studies on the pathways and mechanisms involved on the effects of opioids on GH release show that various types of opioid receptors (μ, κ, δ) are implicated, but their activation effects vary between reports (82,83,84). A reset of the hypothalamic GH pulse generator via opioid receptor stimulation is also a possible mechanism (85).…”
Section: Somatotroph Axismentioning
confidence: 99%
“…(1990) showed that naloxone also decreased GH concentration in heifers. In neonatal rats, stimulation of μ‐ and κ‐opioid receptors resulted in an increase or inhibition of GH release, respectively (Eason et al. 1996).…”
Section: Introductionmentioning
confidence: 99%